Optimalisasi Partisipasi Masyarakat pada Musrenbang Desa Meunasah Teungoh melalui Platform Berbasis Web - Iqbal, Taufiq; Wali, Muhammad; Muliadi, Mus; Muhajir (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2024)
This study aims to enhance community participation in Musrenbang at Meunasah Teungoh Village through a web-based platform. Needs analysis via interviews with 15 village officials and 25 residents in 2024 identified barriers such as one-way communication and limited information access. Developed using React.js and Node.js frameworks, the platform features agenda announcements, digital forms, online discussion forums, and automated email and SMS notifications. Blackbox testing revealed that 95% of features functioned as designed, with an average response time under 2 seconds, ensuring usability for residents with moderate digital literacy. A three-month trial before Musrenbang 2025 resulted in a 45% participation increase (from 120 to 174 participants), 150 community proposals (70% infrastructure, 20% economic empowerment), and 90% user satisfaction. However, 15% of elderly residents faced navigation challenges, indicating a need for additional training. The platform supports e-governance by offering greater transparency and inclusivity compared to conventional methods. Recommendations include enhanced digital literacy training, integration with WhatsApp, and replication in other villages.